1998
DOI: 10.1021/ma981309u
|View full text |Cite
|
Sign up to set email alerts
|

A New Electron-withdrawing Group Containing Poly(1,4-phenylenevinylene)

Abstract: We have synthesized and investigated the electronic properties of poly[2-(2‘-ethylhexyloxy)-5-phenyl-1,4-phenylenevinylene], 12, and its methylsulfonyl derivative poly[2-(2‘-ethylhexyloxy)-5-(4‘ ‘-methylsulfonylphenyl)-1,4-phenylenevinylene], 13. Polymer 13 contains a second-order nonlinear optic chromophore which is in conjugation with the polymer backbone. Polymers 12 and 13 have been used as the electroluminescent (EL) layers in single layer light-emitting diodes (LEDs) (ITO/polymer/Al). We have found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 9 publications
0
38
0
Order By: Relevance
“…It was reported that the HOMO-LUMO energy levels could be lowered for balanced charge injections by the introduction of electron-withdrawing substituents onto the conjugated main chain of the polymer. The electron withdrawing groups such as halide, cyano, trifluoromethyl, or (methylsulfonyl) phenyl were introduced on the arylene rings of PPV derivatives [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the HOMO-LUMO energy levels could be lowered for balanced charge injections by the introduction of electron-withdrawing substituents onto the conjugated main chain of the polymer. The electron withdrawing groups such as halide, cyano, trifluoromethyl, or (methylsulfonyl) phenyl were introduced on the arylene rings of PPV derivatives [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al 7 have found that the HOMO and LUMO energy levels, the electronic and optical properties for some copolymers could be changed with the change of the structures on the main chain and the groups on the side chain. Boardman et al 8 have synthesized a PPV derivative with an electron-withdrawing sulfone group. They believed that there were distinct differences in the optical properties between the parent polymer and its derivative.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the HOMO and LUMO energy levels can be lowered by the introduction of electron-withdrawing groups onto the arylene rings or the vinylene groups of the polymer. 23 To improve the electron injection and the potential efficiency of the polymer LEDs, numerous derivatives of PPV with halide, [24][25][26][27][28] cyano, 29 trifluoromethyl, 30 and methylsulfonyl-phenyl 31 on the arylene rings, or on vinylene, [32][33][34][35] have been reported. The present investigation deals with the synthesis, characterization, photophysics, and electroluminescence (EL) of a new copolymers which contain electron-withdrawing CF 3 F 4 -phenyl group, poly[2-(2-ethylhexyloxy)-5-(2,3,5,6-tetrafluoro-4-trifluoromethylphenyl)-1,4-phenylenevinylene] (CF 3 F 4 P-PPV), and poly[2-(4-(2-etylhexyloxy)-phenyl)-5-(2,3,5,6-tetrafluoro-4-trifluoromethylphenyl)-1,4-phenylenevinylene] (P-CF 3 F 4 P-PPV).…”
Section: Introductionmentioning
confidence: 99%